Seroprevalence and risk factors associated to Bovine Herpesvirus 1 (BHV-1) infection in non-vaccinated dairy and dual purpose cattle herds in Ecuador - Saa, L. (2010)
A cross-sectional study was carried out to determine the seroprevalence and risk factors associated to Bovine Herpesvirus 1 (BHV-1) infection in non-vaccinated dairy and dual purpose cattle herds from Ecuador. A total of 2367 serum samples from 346 herds were collected from June 2008 through February 2009. A questionnaire, which included variables related to cattle, health, management measures and environment was filled out in each herd. A commercial indirect ELISA test was used to determine the seropositivity against BHV-1. Generalized Estimating Equations (GEE) model was used to determine risk factors at individual level, including herd as random effect. The individual seroprevalence to BHV-1 in Ecuador was 43.2% (1023/2367; CI95%: 41.2-45.2%). The herd prevalence was 82.1%; (284/346; CI95%: 78.1-86.1%) and the intra-herd prevalence ranged from 12.5 to 100% (mean=64.1%). The GEE model showed that animal age (>4 years) (OR: 1.44; CI95%: 1.18-1.75), BRSV infection (OR: 1.45; CI95%: 1.09-1.92), altitude over the sea level (?1800m) (OR: 2.97; CI95%: 2.1-4.22) and average slope (>11%) (OR: 1.45; CI95%: 1.07-1.95) are risk factors associated with BHV-1 infection, while a good cleaning of the facilities (OR: 0.66; CI95%: 0.44-0.99) was shown to be a protective factor. © 2011 Elsevier B.V.